Comparative analysis of galectin-1, galectin-3, and galectin-8 signatures in normal and choriocarcinoma trophoblast cell lines - Jovanović Krivokuća, Milica; Legner, Janko; Ćujić, Danica; Vilotić, Aleksandra; Grubiša, Ivana; Vićovac, Ljiljana; Bojić-Trbojević, Žanka (Archives of Biological Sciences, 2024)
Paper description: Expression profiling studies revealed the presence of galectin family members during gestation in the placenta under physiological and pathological conditions. By immunocytochemistry, PCR and Western blotting we investigated the expression and localization patterns of galectins -1, -3, -8 in the normal extravillous HTR-8/SVneo and choriocarcinoma cell lines JAR and JEG-3. Lower expression of galectin-1, -3, and -8 mRNA and protein were observed in JAR and JEG-3 cells compared to HTR-8/SVneo cells. Differences in expression and subcellular distribution suggest galectin involvement in the pathology of choriocarcinoma abundance of the ~40 kDa form in HTR-8/SVneo cells. Abstract: Galectins are found in the placenta during both normal and pathological conditions. Specifically, galectins -1, -3, and -8 have been identified in extravillous trophoblast cells, with galectins -1, and -3 playing notable roles in trophoblast cell function. Altered expression profiles of galectins are linked to various cancers. This study explores the expression and localization of galectins -1, -3, and -8 in a normal extravillous HTR-8/SVneo cell line and two choriocarcinoma cell lines, JAR and JEG-3. Expression levels of these galectins at both mRNA and protein levels were evaluated using PCR, qPCR, and Western blotting, while their cellular localization and distribution were assessed through immunocytochemistry, subcellular fractionation, and Western blotting. Galectins -1, -3, and -8 were expressed at lower levels in JAR and JEG-3 cells compared to HTR-8/SVneo cells. Additionally, different splice variants of galectin-8 were detected across all cell lines. Galectin-1 was predominantly localized at the plasma membrane. Notable differences in galectin-3 localization and distribution were observed between HTR-8/SVneo cells and choriocarcinoma cells. These findings highlight variations in the expression, staining patterns, and subcellular distribution of galectins -1, -3, and -8, suggesting their potential involvement in the pathology of choriocarcinoma.